Unlocking finance for social tech start-ups: Is there a new opportunity space? - Arena, Marika; Bengo, Irene; Calderini, Mario; Chiodo, Veronica (Technological Forecasting and Social Change, 2018)
This paper performs a critical analysis of the financial instruments that can be employed to fund social innovation, with a specific focus on social tech start-ups that develop and deploy technology-driven solutions to address social needs in a financially sustainable manner. The paper analyses how these start-ups can access financing, the barriers to financing that these organisations experience and the financial instruments that are most suitable to address their financial needs. Social tech start-ups have many points of overlap with high-tech start-ups in terms of the barriers they encounter to financing in different lifecycle stages. Still, the institutional solutions that are commonly exploited by high-tech start-ups for growth are not enough to support social tech start-ups to scale. Therefore, we introduce the concept of SII and discuss its potential contribution to the social tech finance landscape. Then, using the case of social tech start-ups as paradigmatic of the broader problem of financing mechanisms for social innovation, we formulate a research agenda, including directions for research and theoretical development in the field of SII.
Keywords: Réservé UdeM; Start-ups